Comparison of quit rates among exclusive cigarette smokers at Tobacco Control Center in Qatar: telephone versus face-to-face consultation - Muslem M. Aljaafar; Silva Kouyoumjian; Gafar Mahmoud; Ahmad AlMulla (BMC Primary Care)
Abstract Background During the coronavirus 2019 pandemic, smoking cessation services were delivered by telephone instead of routine face-to-face care. The objective of this study was to (1) determine if telephone care increases smoking quit rate compared to face-to-face intervention and (2) investigate factors associated with successful smoking cessation. Methods A retrospective study design was utilized. Random selection of patients from two groups (face-to-face care and telephone care) that completed 3 follow-up sessions in Tobacco Control Center in Hamad Medical Corporation in Qatar was conducted from April 2020 to September 2021. Quit rates were compared at 4-week, 8-week and 12-week follow-up visits and a multivariable logistic regression analysis was conducted to obtain factors related to successful quitting at 12-week follow-up. Results A total of 138 patients were included in this study (69 patients for each group). At 12-week follow-up, 31.9% of patients of telephone care (n = 22) succeeded in quitting smoking, while only 20.3% (n = 14) remained abstinent in the face-to-face care group. Telephone care compared with standard care increased the odds of success in stopping smoking (AOR = 3.279; 95% Cl: 1.191–9.026). Also, smokers with a previous quit attempt were significantly related to stopping smoking successfully (AOR = 4.724; 95% Cl: 1.131–19.727). Higher consumption of self-reported cigarette smoking was statistically associated with lower success rates in smoking cessation (AOR = 0.919; 95% Cl: 0.874–0.966). Conclusion Our data suggests that providing telephone care seems more effective in smoking cessation treatment compared with routine face-to-face intervention. However, further formal assessment as randomized clinical trial needs to be conducted for more evaluation.